A Historical Perspective of the La Niña Event in 2020/2021. Issue 7 (5th April 2022) - Li, Xiaofan; Hu, Zeng‐Zhen; Tseng, Yu‐heng; Liu, Yunyun; Liang, Ping
Abstract: El Niño–Southern Oscillation is the strongest interannual variability in the tropical oceans and the major source of global climate predictability. In this work, we examine the evolution of oceanic and atmospheric anomalies in the tropical Pacific during 2020/2021 La Niña and compare it with the historical strong La Niña events since 1982, identify the contributions of different time scale components, and assess the predictions and the impact on extra‐tropical climate. 2020/2021 La Niña emerged in August 2020 and dissipated in May 2021. 2020/2021 La Niña was uniquely preceded by a borderline El Niño instead of an El Niño and a weak equatorial‐heat discharge process. That resulted in the weakest event among the strong La Niñas since 1982, although there were strong upwelling Kelvin wave activities. Moreover, compared with other strong La Niña events, the surface easterly wind anomalies and the warm pool extended further eastward in 2020/2021 La Niña, linking to a relatively weaker dipole‐like pattern of the subsurface ocean temperature anomalies. The strength of all the strong La Niña events is determined by the in‐phase amplification of all time scale variations. Their decay in the boreal spring and early summer is mainly controlled by the intra seasonal‐inter seasonal variation. 2020/2021 La Niña was successfully predicted, however, the North American climate anomalies did not match the typical La Niña response, leading to low prediction skill in the extra‐tropics during its mature phase. Key Points: 2020/2021 La Niña was a strong event and ranks sixth in strength since 1982 2020/2021 La Niña was uniquely preceded by a borderline El Niño instead of an El Niño and a weak equatorial‐heat discharge process 2020/2021 La Niña was successfully predicted, however, and its impacts in North America did not match with a typical La Niña response